2009
DOI: 10.1097/aco.0b013e328323f9a8
|View full text |Cite
|
Sign up to set email alerts
|

Economics and outcome in the intensive care unit

Abstract: Although economic justification should not be the only issue to influence treatments offered in the ICU, increasing use of tools such as cost-benefit analyses is needed to help with medical decisions on the critically ill patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
16
0
3
Order By: Relevance
“…Pittoni and Scatto [39] showed that in severely ill patients the major cost components come from mechanical ventilation and sepsis management, while Dasta et al [40] calculated on the basis of data from 253 US hospitals that mean incremental costs of mechanical ventilation amount to > $US 1.500,00 per day. In a Norwegian University hospital setting, Flaatten and Kvale [41] determined average costs of an ICU day at € 2601,00.…”
Section: Discussionmentioning
confidence: 99%
“…Pittoni and Scatto [39] showed that in severely ill patients the major cost components come from mechanical ventilation and sepsis management, while Dasta et al [40] calculated on the basis of data from 253 US hospitals that mean incremental costs of mechanical ventilation amount to > $US 1.500,00 per day. In a Norwegian University hospital setting, Flaatten and Kvale [41] determined average costs of an ICU day at € 2601,00.…”
Section: Discussionmentioning
confidence: 99%
“…The length of ICU stay contributes a large proportion of financial burden during the whole stay in the hospital (Pittoni & Scatto, 2009;Beenen et al, 2011 ). The gap does exist between the patients families' optimistic expectation and the ICU clinicians' professional judgment and choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, es sabido el elevado costo que tiene la UCI -cercano al 20 % de los costos hospitalarios-, causado esencialmente por la adopción de tecnologías nuevas y por su personal altamente especializado responsable de decisiones de vida o muerte sobre sus pacientes; esto ha forzado a su vez la contención de costos mediante el análisis microeconómico en salud, poniéndose de manifiesto el conflicto entre los intereses individuales y los de la sociedad (21,22). Ahora, las estadísticas relativas a los procesos sociales no son un asunto limitado a lo cuantitativo, pues tales procesos son irreductibles y necesitan, hoy en día, explicaciones cualitativas.…”
Section: La Unidad De Cuidado Intensivo: El Punto De Encuentrounclassified
“…Dado el incremento del costo según la enfermedad por cada día de hospitalización y por cada procedimiento, ¿cuál debe ser la conducta, una individual ajustada a cada caso y su probabilidad de sobrevivir o una colectiva basada en Procedimientos Operativos Estándar -POE-a su vez derivados de Guías de Práctica Clínica potencialmente costosas, inadecuadas y a la larga inefectivas (23)? Siguiendo a Pittoni y colaboradores (22), ¿cuál debe ser el escenario, uno basado en máquinas y tecnología en aras de la vigilancia, o uno donde prime el factor humano en aras del cuidado, o una combinación? ¿Cómo la UCI puede trascender su dependencia histórica de la ventilación mecánica y vencer la sepsis, su archienemigo?…”
Section: La Unidad De Cuidado Intensivo: El Punto De Encuentrounclassified